2022
DOI: 10.1002/rai2.12028
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 vaccine: Attitudes and vaccination in patients with autoimmune inflammatory rheumatic diseases

Abstract: Background We examined attitudes toward the COVID‐19 vaccine, potential factors underlying these attitudes, and ways to increase vaccination willingness in autoimmune inflammatory rheumatic diseases (AIIRD) patients. Methods A multicenter, web‐based, observational survey using an online questionnaire was conducted among AIIRD patients aged ≥18 years from May 24, 2021, to June 3, 2021. Participants were 3104 AIIRD patients (2921 unvaccinated and 183 vaccinated). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…In our previous study, the results demonstrated that 32.9% of AIIRD patients were willing to receive the COVID‐19 vaccine, and the others (67.1%) were uncertain or unwilling, and the main hesitation was that the vaccine may aggravate AIIRD disease (63.0%) and may cause vaccine‐related AEs (19.9%). 7 Overall, although there was some mild AEs after getting the SARS‐CoV‐2 vaccines, the inactivated vaccination is safe, and disease aggravation is needed to pay attention in AIIRDs patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, the results demonstrated that 32.9% of AIIRD patients were willing to receive the COVID‐19 vaccine, and the others (67.1%) were uncertain or unwilling, and the main hesitation was that the vaccine may aggravate AIIRD disease (63.0%) and may cause vaccine‐related AEs (19.9%). 7 Overall, although there was some mild AEs after getting the SARS‐CoV‐2 vaccines, the inactivated vaccination is safe, and disease aggravation is needed to pay attention in AIIRDs patients.…”
Section: Discussionmentioning
confidence: 99%
“…More patients in the AIIRD group took Pregabalin and Gabapentin because of the post-herpetic neuralgia with an insignificant difference (83.3%, 5/6 vs. 40.0%, 2/5, p = 0.242). Similarly, there was no statistical difference for the rash duration (18[12−30] vs. 7[7][8][9][10][11][12][13][14][15][16][17][18][19][20], p = 0.157) and vaccine brand (p = 0.567) between the AIIRD and HCs group. In addition, there was no significant difference in gender, age, comorbidities, time to onset of VZV reactivation and dose of COVID-19 vaccine between AIIRD patients and HCs cohort (p = 0.182, p = 0.314, p = 0.455, p = 0.462, p = 1.000, respectively) (Supporting Information: Table…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The association with DM did not persist on multivariate analysis [58]. Other web-based surveys from China and Egypt did not find an influence of DM on the attitude of patients towards vaccination [62,63]. A Turkish survey of 229 patients with spondyloarthritis and 48 patients with RA found that 36% changed their treatment during the pandemic and that DM was a significant factor for deviation from prescribed drugs [64].…”
Section: Patient Attitude and Behaviorsmentioning
confidence: 96%